Age and fixation strategy as associated factors for sacroiliac joint dysfunction after posterior pelvic ring fixation - Aktan, Cemil; Aktan, Çile; Ergün, Muhammed; Yüksel, Halil Yalçın; Erol, Alpaslan (Frontiers in Surgery, 2025)
BackgroundSacroiliac joint dysfunction (SIJD) is an underrecognized source of postoperative pain and disability after pelvic ring stabilization. Although percutaneous sacroiliac screw fixation provides stable fixation with low morbidity, it restricts physiological SI joint micromotion, potentially causing iatrogenic dysfunction. The relative contributions of injury severity vs. fixation strategy to SIJD remain poorly defined.ObjectivesTo investigate the incidence and factors associated with SIJD after sacroiliac screw fixation for posterior pelvic ring injuries, focusing on fixation laterality (unilateral vs. bilateral) and patient characteristics. Secondary aims included evaluating the functional impact of SIJD on long-term outcomes.MethodsThis single-center retrospective cohort study with prospective follow-up included 80 patients [mean follow-up: 42.3 ± 27.3 months; median 36 months (IQR: 16–56)] who underwent sacroiliac screw fixation between 2016 and 2024. Fracture morphology was classified using Tile and Young–Burgess systems. SIJD was diagnosed prospectively based on ≥3 positive provocation tests. Functional outcomes were assessed using the Oswestry Disability Index (ODI), Visual Analog Scale (VAS), and Lower Extremity Functional Scale (LEFS). Statistical analyses included chi-square, Mann–Whitney U, Cohen's κ, effect sizes (Cohen's d), and multivariate logistic regression.ResultsSIJD occurred in 20 patients (25%), exclusively after unilateral fixation, whereas none followed bilateral fixation (p = 0.004). SIJD-positive patients were younger (32.1 ± 9.0 vs. 41.5 ± 12.8 years, p < 0.001). Fracture morphology showed no consistent association. At ≥12-month follow-up, SIJD-positive patients had worse outcomes (ODI: 37.3 vs. 10.3; VAS: 5.7 vs. 1.6; LEFS: 33.5 vs. 70.3; all p < 0.001). Multivariate analysis identified younger age as an independent predictor (OR 1.8 per decade, p = 0.026).ConclusionsUnilateral fixation is associated with a higher incidence of SIJD, particularly in younger patients. Given the retrospective design, findings should be interpreted as associative and hypothesis-generating rather than confirmatory. Fixation strategy, rather than fracture morphology, appears to be the key associated factor. SIJD causes substantial long-term disability and pain, underscoring the need for individualized fixation planning and prospective validation.Level of evidenceLevel III (Retrospective cohort with prospective follow-up).